Strategi Pemerintah Desa dalam Mewujudkan Ketahanan Pangan di Kalurahan Sidomoyo - Mei Shela, Ilha; Nur Rizki Harahap, Ade; Mei Shela Amanda, Ilha; Dwi Intani, Juwita; Isfaiyah, Siti; Katon Mahendra, Gerry; Gusti Walinegoro, Bhakti (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Food security is a crucial issue at the village level, given its role in improving community welfare. Sidomoyo village has potential in agriculture and fisheries, but as time goes by and population growth increases, farmland in Sidomoyo village is decreasing. This is a challenge for the village government to realize food security in Sidomoyo village. The purpose of this study is to describe and analyze the village government's strategy in realizing food security in Sidomoyo Village. The method used is descriptive qualitative approach, with data collection through interviews, observations, and documentation studies. Based on the research conducted, the village government's strategy in realizing food security in Sidomoyo village is quite good, especially in the aspects of goals and actions. Meanwhile, in the learning indicator, the resulting innovation is still not optimal. Further monitoring, evaluation and mentoring of the training that has been carried out are needed so that the results can be applied effectively. Thus, improvements in the direction and learning indicators are needed to ensure the sustainability of the food security strategy in Sidomoyo Village.